2010
DOI: 10.1186/1471-2164-11-280
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide scan for quantitative trait loci affecting tick resistance in cattle (Bos taurus × Bos indicus)

Abstract: BackgroundIn tropical countries, losses caused by bovine tick Rhipicephalus (Boophilus) microplus infestation have a tremendous economic impact on cattle production systems. Genetic variation between Bos taurus and Bos indicus to tick resistance and molecular biology tools might allow for the identification of molecular markers linked to resistance traits that could be used as an auxiliary tool in selection programs. The objective of this work was to identify QTL associated with tick resistance/susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 40 publications
5
55
2
3
Order By: Relevance
“…And those animals with shorter hairs tend to have lower tick counts compared to those with longer hairs, since long hairs create favourable conditions for tick survival (Taylor et al, 1995;Marufa et al, 2011). Moreover, longer coat hairs may protect ticks from the animal's self-grooming that enables them to remove ticks attached to the coat (Machado et al, 2010). B. indicus were reported to be more innately resistant to B. microplus infestation (Wikel and Whelen, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…And those animals with shorter hairs tend to have lower tick counts compared to those with longer hairs, since long hairs create favourable conditions for tick survival (Taylor et al, 1995;Marufa et al, 2011). Moreover, longer coat hairs may protect ticks from the animal's self-grooming that enables them to remove ticks attached to the coat (Machado et al, 2010). B. indicus were reported to be more innately resistant to B. microplus infestation (Wikel and Whelen, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information regarding this population, including breeding schemes, phenotypic evaluation, and genetic value evaluation processes, was described by Machado et al (2010). Briefly, all animals were ranked by the predicted genetic value for tick resistance.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…No obstante, la lluvia es importante para la taurus breeds, which show greater granulocytic reaction to tick infestations (15), making the Lucerna animals susceptible to this ectoparasite. Likewise, six genes have been identified that provide tick resistance to Gyr x Holstein cattle and are able to offer protection in different seasons (16). Therefore, the animal genetic component affects the impact of tick infestations in a herd, having been reported that Bos taurus cattle and their crosses are less tolerant of ticks and require more intense and costly control programs than Bos indicus cattle (17).…”
Section: Relación Entre Algunos Factores Abióticos Y La Carga Parasitmentioning
confidence: 99%